2007
DOI: 10.1080/03009740701482800
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of FoxP3‐expressing CD4+CD25+T cells with distinct chemokine receptors in synovial fluid of patients with active rheumatoid arthritis

Abstract: There is an accumulation of FoxP3-expressing regulatory T cells in RA SF, and such recruitment may be dependent on the distinct chemokine receptors expressed on regulatory T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
57
0
12

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 31 publications
8
57
0
12
Order By: Relevance
“…The mean (± SD) percentages of CD4+CD25 bright as well as the total CD4+ CD25+ T cells are in line with the published "normal" values [9,16,17]. CD4+CD25+ T cells have been investigated in several autoimmune diseases, presenting conflicting results in most cases [14][15][16][17][18][19][20][21][22]. These discrepancies may be attributed to the differences in the selection of patients (active or inactive diseases) or probably due to technical difficulties in CD4+ CD25+ T cells phenotypic characterization.…”
Section: Fig (2) Percentages Of Cd4+ Cd25supporting
confidence: 85%
See 1 more Smart Citation
“…The mean (± SD) percentages of CD4+CD25 bright as well as the total CD4+ CD25+ T cells are in line with the published "normal" values [9,16,17]. CD4+CD25+ T cells have been investigated in several autoimmune diseases, presenting conflicting results in most cases [14][15][16][17][18][19][20][21][22]. These discrepancies may be attributed to the differences in the selection of patients (active or inactive diseases) or probably due to technical difficulties in CD4+ CD25+ T cells phenotypic characterization.…”
Section: Fig (2) Percentages Of Cd4+ Cd25supporting
confidence: 85%
“…However, Minami et al reported that the percentage of CD4+CD25+ T cells was higher in RA patients than controls, but it was not statistically significant [19]. Other reports showed increased number of these cells in RA synovial fluid but not in peripheral blood [20][21][22].…”
Section: Introductionmentioning
confidence: 95%
“…Similarly, the absence of Treg cells in K/BxN scurfy mice is associated with faster onset and greater severity of arthritis (16). The proportion of Treg cells in RA patients is increased in the synovium but unchanged in the peripheral blood, when compared to that in healthy individuals and patients with other joint diseases (17,18). Importantly, the Treg cell phenotype and suppressive activity of Treg cells are altered in RA.…”
mentioning
confidence: 99%
“…This hypothesis seems to be further supported by investigations of the correlation between the percentage of Treg cells in PB and disease duration, which have confirmed higher numbers of circulating Treg cells in patients with long-standing disease [35,39]. Moreover, in established disease, where proinflammatory cytokines, including TNFα, are present at high levels in PB and target organs, FoxP3 expression within the CD4 + CD25 + cell population seems to be reduced, giving rise to the hypothesis that proinflammatory molecules play a role in inducing an abnormal Treg cell phenotype [37,40].…”
Section: The Paradox Of Treg Cell Expansion In Ra Patientsmentioning
confidence: 73%